2022
DOI: 10.3390/cells11081268
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of BPV-1 Mediated Matrix Metalloproteinase Genes Deregulation in the In Vivo and In Vitro Models Designed to Explore Molecular Nature of Equine Sarcoids

Abstract: Matrix metalloproteinases (MMPs) represent a family of enzymes capable of biocatalytically breaking down the structural and functional proteins responsible for extracellular matrix (ECM) integrity. This capability is widely used in physiological processes; however, imbalanced MMP activity can trigger the onset and progression of various pathological changes, including the neoplasmic transformation of different cell types. We sought to uncover molecular mechanisms underlying alterations in transcriptional profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In this context, it is interesting to mention that in bovine cutaneous fibropapillomas, we demonstrated by immunohistochemistry a weak to moderate cytoplasmic and perinuclear collagenase MMP-1 expression, comparing to normal skin samples where a moderate reaction was seen; these differences in expression normal vs. tumors were confirmed biochemically, suggesting a potential contribution by potentiating the collagenolysis process. However, a recent study on in vivo and in vitro models designed to explore molecular nature of equine sarcoids indicate that BPV-1 infection contributes to diminished MMP-1 expression level ( 33 ), results which are consistent with our study. On the other hand, in knockdown MMP-1 cervical cancer cell lines it has been demonstrated a reduced invasion ability compared to the control, suggesting that knockdown of MMP-1 is responsible of reduced proliferation, invasion and migration ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this context, it is interesting to mention that in bovine cutaneous fibropapillomas, we demonstrated by immunohistochemistry a weak to moderate cytoplasmic and perinuclear collagenase MMP-1 expression, comparing to normal skin samples where a moderate reaction was seen; these differences in expression normal vs. tumors were confirmed biochemically, suggesting a potential contribution by potentiating the collagenolysis process. However, a recent study on in vivo and in vitro models designed to explore molecular nature of equine sarcoids indicate that BPV-1 infection contributes to diminished MMP-1 expression level ( 33 ), results which are consistent with our study. On the other hand, in knockdown MMP-1 cervical cancer cell lines it has been demonstrated a reduced invasion ability compared to the control, suggesting that knockdown of MMP-1 is responsible of reduced proliferation, invasion and migration ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…MMP-14 or MT1-MMP was originally identified as the extracellular protease responsible for activation of pro-MMP-2 ( 19 ). Interestingly, in BPV positive equine sarcoid an up-regulation of MMP-14 was demonstrated in several studies, which can explain the sarcoids' very or negligibly low capability to metastasize ( 15 , 20 ). Moreover, in human counterpart, Akgül and co-workers (2006) showed that expression of the HPV- 8 caused overexpression of MMP-14, suggesting a role of this MMP in the development of HPV-8 induced cutaneous tumors ( 9 ).…”
Section: Introductionmentioning
confidence: 97%
“…Such high differences can indicate that ECM remodeling occurs, as in both human cancers and equine sarcoids. Interestingly, the previous study performed on sarcoids confirmed the significant over-expression of both MMP2 and MMP9 genes in the tumor tissue and in cell lines transfected with BPV-1 gene construct [ 31 ]. These findings strengthen the hypothesis that one of the main mechanisms responsible for sarcoid formation can be the FN1 –matrix metalloproteinase axis.…”
Section: Discussionmentioning
confidence: 87%
“…To establish DEGs involved in ECM remodeling and cell adhesion pathways, two sets of data obtained from our previous investigations were used (GSE193906 and GSE83430) [ 31 , 50 ]. The raw data annotated as GSE193906 were generated via NGS sequencing of two groups encompassing ACFC lines transfected with the BPV1-E1^E4 gene construct and control (i.e., non-transfected) ACFC lines.…”
Section: Methodsmentioning
confidence: 99%